Synthesis, Characterization, Molecular Docking, Synthesis and biological activity of Schiff bases derivatives derived from Ceftriaxone as Anti-PC3 - Asmaa A. Jawad1 (Al-SalamJournal for Medical Science)
Schiff bases are formed by reacting aromatic or aliphatic ketones or aldehydes with heterocyclic amines, yielding azo methine derivatives. The ceftriaxone reacts with aldehydes, such as 4-(N, N-dimethylamino) benzaldehyde and 4-heptoxybenzaldehyde, giving new schiff bases derivatives and characterization by FTIR. These derivatives (A and B) tested for in vitro biological activity against Bacillus subtilis, Streptococcus pneumonia, E. coli, Bacillus subtilis, Candida, and Aspergillus nigaer. The biological properties of derivatives A and B have been evaluated against different bacteria and fungi. Docking is crucial for examining binding mechanisms. The function of GP6 synthase in the formation of microbial cell walls. Both compounds had similar binding affinities, with ceftriaxone measuring -6.9 kcal/mol. Experiments confirm that both substances possess antibacterial properties. The derivative A has a more pronounced influence on suppressing bacterial growth in petri dish zones. The most substantial effect on fungus was seen in the case of Aspergillus niger due to derivative A. The cytotoxic effect of the prepared Ceftriaxone derivatives against human prostate cancer cells (PC3) was investigated using the MTT colorimetric assay. The cytotoxicity assay reveals that the B (heptoxybenzaldehyde Ceftriaxone derivative) is more active to inhibit the growth of PC3 cells compared to the A (N, N-dimethylamino) benzaldehyde Ceftriaxone derivative).